Pengembangan Pariwisata Dan Dampak Sosial Ekonomi Di Bandar Lampung - Muhammad Luthfi (Universitas Malahayati, 2013)
Tourism is an activity trip or part of these activities are voluntary and temporary objectsand to enjoy the tourist attraction of tourism sector is a significant source of foreign exchange and thepercentage contribution to the local treasury , which is widely also a source of foreign exchange. Thecapital city of Bandar Lampung province with an area of 197.22 km2 comprised of 13 districts and 98villages . This study aims to determine the development of tourism in the economic and social impactof Bandar Lampung . The results showed a relationship attraction development and socio-economicimpact is low at 15.70 % means that tourism development does not have an impact on the socioeconomicsituation in Bandar Lampung . The role of local governments is needed in this case in theform of policy and as a mediator between citizens about the location of the employer attractionattractionKeywords; economic and social attraction